INDONESIA’S NATIONAL POLICY ON OFFSHORE MINERAL RESOURCES: SOME LEGAL ISSUES - Kusumaatmadja, Mochtar (UI Scholars Hub, 2013)
There are many legal issues arising from the field offshore mineral resources activities, one of them is about the ownership of the resources and the right to explore and exploit. This article discusses the historical background of the law governing offshore resources in Indonesia and then completed by the current development of this field.